The new normal and its impact on society: perspectives from ASEAN and the European Union - Nurliana Kamaruddin; Aida Idris; Fernandez, Kevin (Palgrave Macmillan, 2024)
Chapter 1 Introduction -- Chapter 2 Changing demographics and its impact -- Chapter 3 The lost generation in ASEAN and EU -- Chapter 4 Work and employment patterns -- Chapter 5 Cybercrimes and cybersecurity -- Chapter 6 Migration, refugee, and international mobility -- Chapter 7 Human capital development -- Chapter 8 The Way Forward.